2016
DOI: 10.1016/j.jphotobiol.2016.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Rose bengal uptake by E. faecalis and F. nucleatum and light-mediated antibacterial activity measured by flow cytometry

Abstract: Rose bengal uptake by E. faecalis and F. nucleatum and light-mediated antibacterial activity measured by flow cytometry Antibacterial photodynamic therapy (aPDT) using rose bengal (RB) and blue-light kills bacteria through the production of reactive oxygen derivates. However, the interaction mechanism of RB with bacterial cells remains unclear. This study investigated the uptake efficiency and the antibacterial activity of blue light-activated RB against Enterococcus faecalis and Fusobacterium nucleatum. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…aureus was treated with curcumin and illuminated for 60 min, 28Á31% of dead cells were obtained, while the control containing only the bacteria had 1Á27% of dead cells (Jiang et al 2014). Manoil et al (2016) reported 2% of dead cells in the control containing only Ent. faecalis and 3Á5% in F. nucleatum, but after treatment with rose bengal and irradiation for 240 s 98Á8% of dead cells were obtained for Ent.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…aureus was treated with curcumin and illuminated for 60 min, 28Á31% of dead cells were obtained, while the control containing only the bacteria had 1Á27% of dead cells (Jiang et al 2014). Manoil et al (2016) reported 2% of dead cells in the control containing only Ent. faecalis and 3Á5% in F. nucleatum, but after treatment with rose bengal and irradiation for 240 s 98Á8% of dead cells were obtained for Ent.…”
Section: Discussionmentioning
confidence: 95%
“…Manoil et al . () reported 2% of dead cells in the control containing only Ent. faecalis and 3·5% in F. nucleatum, but after treatment with rose bengal and irradiation for 240 s 98·8% of dead cells were obtained for Ent.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations